STUDIES ON NUTRITIONAL PROFILE AND ANTIOXIDANT POTENTIAL OF DIFFERENT DIOSCOREA SP WITH PLECTRANTHUS ROTUNDIFOLIUS - Joy, Jenit K.; Siddhuraju, P. (International Journal of Current Pharmaceutical Research, 2017)
Objective: Protection from oxidative damage to the tissues is provided by natural or synthetic antioxidants. Because of the multiple mechanisms of actions and presence of various phytochemicals, plant-based antioxidants are preferred. Dioscorea is well known as a traditional edible tuber. The present study was undertaken to explore and highlights the nutritional benefits and to evaluate the in vitro antioxidant and free radical scavenging capacity of ethanolic extract of three different underutilised Dioscorea species (D. alata, D. pentaphylla and D. oppositifolia) with a common cultivated crop, Plectranthus rotundifolius. Methods: Different processing methods are adopted to assess their influence on nutritive value and antioxidant properties. Tubers were studied for proximate composition using standard analytical methods. Mineral elements were analysed using ICP-MS (Inductively Coupled Plasma-Mass Spectrometer). Antioxidant potential of raw and processed samples was determined using a range of in vitro models. Results: The presence of essential minerals such as Na, K, Ca, P, Zn and Mn were observed. High radical scavenging activity was observed in the tubers of Dioscorea. Results indicated that phenolic compounds are the significant contributors to the antioxidant activity. Conclusion: Current study suggests that Dioscorea might be a promising natural antioxidant and could be very useful health food, as they enhance the antioxidant defence system. It also proposes that underutilized tubers can efficiently contribute to the nutritional requirement and food security.Â